2008
DOI: 10.1007/s10517-008-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-casomorphin-7 on DNA synthesis in cell populations of newborn albino rats

Abstract: We studied the effect of beta-casomorphin-7 on DNA synthesis in cell populations of newborn albino rats. Intraperitoneal administration of a beta-casein fragment heptapeptide beta-casomorphin-7 (1 mg/kg, 1 or 5 injections) activated proliferative processes in the myocardium and ectodermal and endodermal epithelium of newborn rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…C: Administration (i.p.) of either: (a) BCM-4, (b) BCM-6, or (c) distilled water Single dose of either I or C with the following concentrations: 1 mg/kg, 5 mg/kg, or 20 mg/kg Neurological effect*: behavioural change (locomotor activity) Not reported 16 Maslennikova 2008 [ 37 ] Russia 42 new-born outbred albino rats, aged 2–4 days To evaluate the effect of BCM7 on DNA synthesis in cell populations (tissue) of new-born albino rats I: BCM-7 administration (i.p.) C: Administration (i.p.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…C: Administration (i.p.) of either: (a) BCM-4, (b) BCM-6, or (c) distilled water Single dose of either I or C with the following concentrations: 1 mg/kg, 5 mg/kg, or 20 mg/kg Neurological effect*: behavioural change (locomotor activity) Not reported 16 Maslennikova 2008 [ 37 ] Russia 42 new-born outbred albino rats, aged 2–4 days To evaluate the effect of BCM7 on DNA synthesis in cell populations (tissue) of new-born albino rats I: BCM-7 administration (i.p.) C: Administration (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…Chang et al found increased growth performance with the administration of BCM-7 and described the involved mechanisms in broiler chickens [ 24 ]. Similarly, one study showed that BCM-7 stimulated DNA synthesis in new-born rats [ 37 ]. Furthermore, Wei et al found no effect of BCM-7 on the heart rate of rats (acting as opioid agent) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Накопление метки составляло десятые и сотые доли процента от введенного количества, однако было вполне достоверным. Накопление метки не зависит прямо от количества введенного вещества, что, в определенной степени может свидетельствовать о существовании особой транспортной системы, которая играет значение в переносе β -КМ через ГЭБ [8,9,10].…”
Section: проникновение β-км через гематоэнцефалический барьерunclassified
“…[49] Modulation of gene expression of the regulatory peptides from G and D cells was also demonstrated and data from in situ hybridization studies indicated that BCM-7 affected gastrin gene expression indirectly by means of the paracrine action of somatostatin. [9] Maslennikova et al [50] have found that BCM-7 was responsible for ex-vivo activation (DNA synthesis) of proliferative processes in the myocardium and ectodermal and endodermal epithelium of newborn rats. Orally administered BCM-7 has been demonstrated to influence postprandial metabolism by stimulating secretion of insulin.…”
Section: Functional Importance Of Bcm-7mentioning
confidence: 99%